A longer-term perspective on human exploitation and management of peat wetlands: the Hula Valley, Israel - R.J. Payne (Mires and Peat, 2012)
The influence of non-recent human activities on the structure and functioning of wetlands is frequently overlooked. The Hula wetland in northern Israel was exploited for a variety of resources over thousands of years prior to near-total destruction by drainage in the 1950s. These pre-drainage human impacts created a mosaic of anthropogenic habitats which should be considered in attempting to re-create and rehabilitate the wetlands. Here we take an environmental history approach, using the documentary record to identify the numerous ways in which the ecosystem was shaped by human activity. The major traditional activities in the wetland included reed-harvesting, fishing, animal husbandry and limited arable agriculture. The corpus of material examined illustrates that drainage of the wetlands has a longer history than is frequently supposed. Activities such as papyrus harvesting, buffalo husbandry and fishing shaped the ecosystem and their replication may be desirable to re-create lost anthropogenic niches in contemporary conservation management.